2015
DOI: 10.5194/acp-15-13787-2015
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric radar and in situ observations of riming and snowfall microphysics during CLACE 2014

Abstract: Abstract. This study investigates the microphysics of winter alpine snowfall occurring in mixed-phase clouds in an inner-Alpine valley during January and February 2014. The available observations include high-resolution polarimetric radar and in situ measurements of the ice-phase and liquidphase components of clouds and precipitation. Radar-based hydrometeor classification suggests that riming is an important factor to favor an efficient growth of the precipitating mass and correlates with snow accumulation ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 48 publications
2
81
0
Order By: Relevance
“…This finding is consistent with the observations using polarimetric radar data reported by Mott et al () who identified local enhancement of snowfall around mountain ridges and summits due to the occurrence of rimed snow aggregates and graupel. Evidence of riming in alpine snowfall has been also reported by Grazioli et al () even if they do not discuss in details the spatial variability of precipitation generated by riming. The differences in terms of spatial variability between graupel and snow aggregates in our study depend partially on assumptions made in the cloud microphysical scheme used in Meso‐NH (Pinty & Jabouille, ).…”
Section: Resultsmentioning
confidence: 90%
“…This finding is consistent with the observations using polarimetric radar data reported by Mott et al () who identified local enhancement of snowfall around mountain ridges and summits due to the occurrence of rimed snow aggregates and graupel. Evidence of riming in alpine snowfall has been also reported by Grazioli et al () even if they do not discuss in details the spatial variability of precipitation generated by riming. The differences in terms of spatial variability between graupel and snow aggregates in our study depend partially on assumptions made in the cloud microphysical scheme used in Meso‐NH (Pinty & Jabouille, ).…”
Section: Resultsmentioning
confidence: 90%
“…Harimaya and Sato [] estimate that this value is higher for the coastal region of Japan and ranges between 50% and 100%. Grazioli et al [] have shown that there seems to be a correlation between occurrence of riming and precipitation accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Mitchell et al [] and Harimaya and Sato [] have shown that riming could explain 30% to 100% of surface snowfall mass. Furthermore, Grazioli et al [] have found that there is also an apparent positive correlation between a precipitation rate and riming occurrence during winter storms.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation in midlatitudes originates mostly from mixed‐phase cloud systems and growth of ice particles by the collection of supercooled liquid drops. This process, known as riming, contributes significantly to surface precipitation, see e.g., Grazioli et al () or Moisseev et al () for some observational evidence based on state‐of‐the‐art measurement techniques. For example at the coastal areas of Japan, heavily rimed snow particles are in fact present in more than 70% of the snowfall events and contribute more than 50% to wintertime surface precipitation (Harimaya & Sato, ).…”
Section: Introductionmentioning
confidence: 99%